1996
DOI: 10.1007/bf00182065
|View full text |Cite
|
Sign up to set email alerts
|

Polytetrafluoroethylene sling for failure in female stress incontinence surgery

Abstract: Surgery for stress urinary incontinence (SUI) in women with previous interventions is often difficult and yields poor results. A total of 33 women with recurrent SUI underwent placement of a polytetrafluoroethylene (PTFE) sling after a mean of 1.5 (range, 1-3) unsuccessful operations. Preoperative bladder instability (BI) was ruled out in all cases. The patients' mean age was 54 (range, 34-79) years. In all, 64% had SUI and 36% had SUI and incontinence at rest. The Aldrige-Stoeckel technique is used with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The reported incidence of sling material erosion used during pubovaginal sling placement is 0.3% to 23% and autologous material has the lowest rate [13]. For expanded polytetrafluoroethylene slings, rejection rates of 6-32% have been reported [14,15]. A similar rejection rate has been reported for polyethylene slings [16].…”
Section: Discussionsupporting
confidence: 53%
“…The reported incidence of sling material erosion used during pubovaginal sling placement is 0.3% to 23% and autologous material has the lowest rate [13]. For expanded polytetrafluoroethylene slings, rejection rates of 6-32% have been reported [14,15]. A similar rejection rate has been reported for polyethylene slings [16].…”
Section: Discussionsupporting
confidence: 53%
“…The use of Gore-tex slings has been well described in adult women with stress urinary incontinence [11][12][13]. The main complications reported include temporary urinary retention needing CIC, urge incontinence, and less commonly erosion into the urethra.…”
Section: Discussionmentioning
confidence: 99%
“…The main complications reported include temporary urinary retention needing CIC, urge incontinence, and less commonly erosion into the urethra. Short-to moderate-term followup has yielded high continence rates [11][12][13]. A Cochrane database review found the Goretex sling to have a higher complication rate than fascial slings for urinary incontinence in women in a small series of patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…151 Other more serious infections have been reported after SMUS implantation. In a comprehensive literature review 45 several such complications following sling placement were reported: cellulitis; [117][118][119][120][121]187 abscess formation, including in the retropubic space, 122 retroperitoneal space, 123 thigh, 123 obturator space [124][125][126] and ischiorectal fossa; 127,128 sinus tract formation; 129 necrotizing fa sciitis; 130 osteitis pubis; 131 and sepsis. 12 Thigh abscesses, a complication unique to the TOT sling approach, have been reported in the past decade.…”
Section: Reviews Infectionmentioning
confidence: 98%
“…In addition, we estimate that bowel perforation and serious infections have a combined incidence of about 0.1%. [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134] Refractory and potentially lifestyle-altering complications include chronic pain (4.1%) and de novo overactive bladder (OAB) in 11% (Table 5), although the number of patients with de novo OAB who are refractory to treatment remains unknown. Evidence suggests that well over 50% of patients with OAB of any aetiology discontinue medical treatment within 1 year, owing to a combination of poor effectiveness and low tolerability.…”
Section: Smus Complicationsmentioning
confidence: 99%